The Effect of Self-Efficiency and Organizational Justice On Lecturers' Career Development With Work Motivation as A Variable Mediation At Muhammadiyah Higher Education In DKI Jakarta - Yusuf, M.; Haryoto, Cecep; Husainah, Nazifah (Green Publisher Indonesia, 2022)
This study aims to determine the effect of self-efficacy and organizational justice on the career development of lecturers with work motivation as a mediating variable at Muhammadiyah College in DKI Jakarta. This study uses an associative method with a quantitative approach, with a total of 179 lecturers at Muhammadiyah Higher Education in DKI Jakarta. The results of the study show that (1) self-efficacy has a positive and significant effect on the work motivation of lecturers at Muhammadiyah Higher Education in DKI Jakarta, (2) organizational justice has a positive and significant effect on the work motivation of lecturers at Muhammadiyah Higher Education in DKI Jakarta, (3) Self-efficacy has a positive and significant effect on the career development of lecturers at Muhammadiyah Higher Education DKI Jakarta, (4) Organizational justice has a positive and significant effect on lecturer career development at Muhammadiyah Higher Education in DKI Jakarta, (5) Work motivation has a positive and significant effect on lecturer career development at Muhammadiyah Higher Education in DKI Jakarta, (6) Self-efficacy has a positive and significant effect on lecturer career development through work motivation at Muhammadiyah Higher Education in DKI Jakarta, and (7) Organizational justice has a positive and significant effect on lecturer career de development through work motivation in a Muhammadiyah College in DKI Jakarta